Pengaruh Transitory Earnings Pada Penggunaan Rasio E/p Dalam Penilaian Perusahaan: Studi Empirik Di Indonesia - Erni Ekawati (Fakultas Bisnis UKDW, 2010)
The purposes of this study are, firstly, to confirm the findings of the previous study, whether earnings contain transitory component. Secondly, to investigate how E/P ratios are affected when firms experience transitory earning changes. Thirdly, tg examine whether the dffirences in E/P ratios across firms-due to differences in the magnitude of transitory earnings will quickly disappear in subsequent years. (Jsingfinancial dan of companies listed in Jakarta Stock Exchange (JSE).from the periods of 1993 to 2003, the study finds that earning changes etehibit a transitory component. Under the condition of transitory earnings, .fir*'t E/P ratio is positively affected by the changes in earnings. Industry-adjusted earning changes variable is shown to have a high explanqtory power in predicting-firm's E/P ratio. As the variation offirm's E/P ratios are mainly explained by the transitory component of earnings, time series pattern of E/P ratios reflects transitory deviations due to the transitorycomponent of earnings changes.